Effect of heat treatment on microstructures and mechanical properties of A356 alloy cast through rapid slurry formation (RSF) process. (3rd September 2017) - Gupta, Robin; Sharma, Ashok; Pandel, Upender; Ratke, Lorenz
Abstract: The effect of T5 heat treatment on microstructure and mechanical properties of A356 alloy was observed. The as-cast A356 alloy exhibited coarse dendrites and long Si needles. RSF process changed the dendritic α-Al phase to globular morphology which helps in improving the mechanical properties of the alloy. The addition of 0.6wt-% Al–5Ti–1B grain refiner refined the average grain size of primary α-Al phase. T5 heat treatment at 170 °C for 20 h in different processing conditions was given to A356 alloy. T5 heat treatment led to further refinement of α-Al phase and Si needles, precipitation hardening due to Mg2 Si phase and reduction in the porosity level (%). The Quality Index for A356 alloy in different processing conditions was also measured. Results showed that RSF process with the use of baffles, addition of grain refiner and T5 heat treatment had improved the mechanical properties over other processing conditions.